ENHANCING LETTER RECOGNITION THROUGH PLAYING PLASTICIN IN GROUP A PAUD TERPADU QATHRUN NADA BANJARMASIN - Amelia, Amelia (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2023)
The background of this research is the low cognitive development of children in recognizing letters caused by the less attractive learning strategies and media used. The solution used to improve children's ability to recognize letters is through playing with plasticine. The aim of this research is to improve learning to increase children's ability to recognize letters. This research used the Classroom Action Research (PTK) method which was carried out in 2 cycles with research subjects of 9 children in group A of Integrated PAUD Qathrun Nada Banjarmasin. Based on the results of research conducted, playing with plasticine can increase teacher activity by up to 97%, children's activity reaches 100%, and children's ability to recognize letters reaches 100%. Based on these results, it can be concluded that playing plasticine can improve children's ability to recognize letters in group A of Integrated PAUD Qathrun Nada Banjarmasin.